EFEKTIVITAS STRATEGI PROMOSI PADA KSU AL KAHFI DALAM MENINGKATKAN JUMLAH NASABAH DEPOSITO PROMO - ambarsari, nita; fitria, norma (Irtifaq, 2020)
This article aims to describe the efforts of KSU Al-Kahfi Jombang in increasing the number of promo deposit customers and using qualitative methods with observation, interviews and documentation as data collection techniques and then analyzed descriptively. The results showed that the promotion strategy of the Deposito Promo product in increasing the number of customers at KSU Al-Kahfi Jombang was said to have been effective. There are positive changes which have occurred during the last 4 years. In addition, customers of the KSU Al-Kahfi Jombang Deposit Promo products are also able to have a good impact on their business performance. Keywords: Effectiveness, Promotion Strategy